Ideas of hesychasm in russian philosophy: protective and cre ative aspects - V.O. Morgachev (Advanced Engineering Research)
In article the author tries to trace first of all the connection of XIX - XX centuries Russian religious philosophy and hesyhasm as an orthodox mystic and ascetic tradition (experience of deep prayer) based on materials of the research of history of philosophy and Religion Studies by professor S.S. Khoruzhy and works of outstanding Russian thinkers as I.V. Kireevsky, K.N. Leontyev, P.A. Florensky, A.F. Losyev, I.A. Ilyin. Secondly, this research reveals the hesyhasm influence on the protective and creative aspects of studies thinkers ideas based on the concept of the monk Vsevolod (Phylippiev), modern Church historian.